EFISIENSI TEKNIS DAN KETAHANAN PANGAN RUMAH TANGGA PETANI UBIKAYU DI PROVINSI LAMPUNG - Indah, Lidya Sari Mas; Zakaria, Wan Abbas; Murniati, Ktut (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
The objectives of this study are (1) to analyze technical, economic and price efficiency and inefficiency, (2) to analyze household food security of cassava farmers.  The cassava production center of East Lampung Regency was selected purposively with total sample of 60 cassava farmers using simple random sampling.  Data were collected in December 2021.  The research method was a survey, using primary and secondary data.  Data were analyzed using the stochastic frontier production function with the Frontier 4.1 program, and the level of food security categorized based on FAO and Law of the Republic of Indonesia No. 7 of 1996.  The calculated average results show that the levels of technical efficiency (TE), allocative efficiency (AE), and economic efficiency (EE) of cassava farmers in East Lampung are 86 percent, 100 percent, and 100 percent respectively.  This shows that the existing agricultural resources can increase average production efficiency by 14 percent each for technical efficiency, while allocative efficiency and economic efficiency have reached a maximum in the very efficient category.  The findings also indicate that the variables of land area, KCl fertilizer, and organic fertilizer have a significant effect on cassava production.  The variable factors that influence the technical inefficiency factor in East Lampung are farmer group participation, and the distance to the factory.  The food security category in this study is 73.33 percent of farming households categorized as unsafe, and 26.67 percent are categorized as less safe.  This study concludes that resource allocation by farmers is inefficient.  Therefore, the efforts to increase productivity must be followed by an efficient use of resources to have a significant impact on the food security of farmer households, and to develop strategic implications for farmer welfare. Keywords:  cassava, food security, production efficiency